THE INFLUENCE OF THE CONDITION OF TEETH AND A SMILE ON A PERSON'S SELF-ESTEEM AND CONFIDENCE - Yusufbek , Rashidov; Haydarova, Dilfuza (Uzbekistan Open Conference, 2025)
The article examines the relationship between the condition of teeth, the aesthetics of a smile and the level of self-esteem of a person. The psychological and social aspects of the perception of a smile in interpersonal communications are analyzed. Special attention is paid to the role of dental health in shaping the confidence of an individual, its social status and quality of life. The paper presents the results of domestic and foreign studies confirming that the aesthetic appeal of a smile is directly related to psychological well-being.
Keywords: smile; self-esteem; confidence; dentistry; psychology; aesthetics; interpersonal perception